Periodos y dosis óptima de aplicación de extracto de Barbasco (Lonchocarpus nicou), para el control de Stemphylium solani en Tomate en la localidad de Lamas. - Moreno Pizarro, Percy Humberto (2008)
In order to determine the optimal dese of barbasco aqueous implementation extract (1:1), for control of Stemphylium solani in growing this tomato-level field in the province from Lamas. Using the design of randomized complete block (DBCR), with 3 replicates and 10 treatments were applied dose of 25 mi, 40 mi, 60ml extract barbasco / liter of water every 8, 1 O and 15 days respectively. The parameters were evaluated: incidence of the disease, severity of illness (Scale of Lee Campbell and Laurence V. Madden 1990), Share performance (Formula amended Abbot), number of flowers to plant, number of dead flowers to plant, number of fruit to plant, yield to Kg for treatment. All treatments studied have researched an incidence of 100% at 13 days after T7 (60 mi of extract with application every 8 hours), showed an efficiency of 77%; treatments T1 (25 mi of extract with apptication every 8 hours) and T6 (40 mi of extract with application every 15 days) obtained the largest number of flowers for plant with 35.5 and 35.67 respectively on average; treatments T3 (25 mi of extract with application every 15 days) and T10 (60 mi of extract with application every 8 days }, yielded the highest retums with 36 880 Kg. I ha, 18 100 Kg. J ha respectively.